2016
DOI: 10.1093/bioinformatics/btw464
|View full text |Cite
|
Sign up to set email alerts
|

Edge-based sensitivity analysis of signaling networks by using Boolean dynamics

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Whereas nFC measures the similarity of activity between two brain regions -a first-order correlation [49] -eFC measures the similarity of co-fluctuations between edge pairs -a higher-order correlation [36]. Understanding the higherorder organization of networks has proven useful in other disciplines [40,41,50,51]. Here, adopting an edge-centric perspective allows us to link higher-order brain network organization with subject specific features.…”
Section: Edge Functional Connectivity Enhances Subject Identifiabilitymentioning
confidence: 99%
“…Whereas nFC measures the similarity of activity between two brain regions -a first-order correlation [49] -eFC measures the similarity of co-fluctuations between edge pairs -a higher-order correlation [36]. Understanding the higherorder organization of networks has proven useful in other disciplines [40,41,50,51]. Here, adopting an edge-centric perspective allows us to link higher-order brain network organization with subject specific features.…”
Section: Edge Functional Connectivity Enhances Subject Identifiabilitymentioning
confidence: 99%
“…The edgecentric representation shifts focus away from dyadic relationships between nodal activations and onto the interactions between edges (the similarity in their patterns of cofluctuation, a potential hallmark of communication), instead. While similar models have been explored in other scientific domains [19][20][21][22], they require as input sparse node-node connectivity matrices and are poorly suited for continuous-valued time series data, making them suboptimal representations of dynamic neural data.…”
Section: Edge-centric Perspective On Functional Network Organizationmentioning
confidence: 99%
“…A limitation of the node-centric approach is that it cannot capture potentially meaningful features or patterns of interrelationships among edges. In other scientific domains, prioritizing network edges, for example by modeling and analyzing edge-edge interactions as a graph, has provided important insights into the organization and function of complex systems [19][20][21][22]. In contrast, with few exceptions [23], network neuroscience has remained focused on nodal features and partitions, paralleling a * rbetzel@indiana.edu rich history of parceling, mapping, and comparing cortical and subcortical gray matter regions [24].…”
Section: Introductionmentioning
confidence: 99%
“…We need to extensively simulate randomly structure networks to verify that the new findings in real networks are generally conserved. In this study, we employed a shuffling model to generate random networks [ 10 , 18 ]. Given a reference network, it rewires some edges in a way that in-degree and out-degree of every node are conserved.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a few studies showed that the modularity is greatly changed by the removal of hubs [ 9 ] or by stabilizing events in protein–protein interaction networks. Some other studies also proved that the robustness is considerably changeable according to a variety of mutations [ 10 13 ]. Additionally, there were some previous studies to investigate a relation between the robustness and the modularity.…”
Section: Introductionmentioning
confidence: 94%